The Identification of Quem Non Prevalent in Klosterneuburg, Augustiner-Chorherrenstift – Bibliothek, 1013 - Debra Lacoste (De Musica Disserenda, 2015)
Of the thirty-six occurrences of responsory tropes in the eight earliest Klosterneuburg antiphoners, Quem non prevalent is found only once, in A-KN 1013. Its placement apart from its host responsory and the lack of rubrics have masked its usage, but an analysis of its melodic and textual features clarifies its purpose.